Genesis of the Planet Earth - Orlov, S. (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2016)
This article is based on the theory of vortex gravitation and physical abnormalities of the Earth slowing its rotation. Defined orbital acceleration, weight, approach to the Sun and the age of our planet. Offered to justify the creation of planetary material in the center of the Earth torsion, and not as the accumulation of cosmic dust and meteorites from outer space.